Physicochemical and thermal characteristics of sugarcane straw and its cellulignin - Canettieri, Eliana Vieira [UNESP]; da Silva, Vinícius Pereira; Neto, Turíbio Gomes Soares; Hernández-Pérez, Andrés Felipe; da Silva, Debora Danielle Virgínio [UNESP]; Dussán, Kelly Johana [UNESP]; das Graças Almeida Felipe, Maria; de Carvalho, João Andrade [UNESP] (Springer Nature, 2018)
Combustion of biomass is considered to be a source of atmospheric pollution and, therefore, is one of the important sources of CO2 emission. This paper discusses the burning of sugarcane straw and its cellulignin in laboratory tests to determine the characteristics and emission factors, of this combustion process. Elemental, chemical composition and thermogravimetric analyses were performed for both samples. Carbon contents for sugarcane straw and its cellulignin were estimated, and the values found were 45.69% and 44.28%, respectively. Higher heating values (HHV) were determined by experimental methods with a calorimetric bomb and were estimated by theoretical equations. The best results were obtained when only the lignin’s content was considered. During the experimental tests to determine HHVs, cellulignin did not burn completely, while straw burned completely. This could be because cellulignin contains more ashes, resulting in more residual ash after burning. Pollutant emission of CO2, CO, NO and UHC was evaluated in the flaming and smoldering combustion phases. NO concentrations were not presented because they were less than 10 ppm. The average theoretical and experimental emission factors for CO2 were analyzed. CO2 emissions factors found for sugarcane straw and their cellulignin were 1316 ± 83.6 and 1275 ± 105 g kg−1 of dry burned biomass, respectively. The evaluated parameters are useful to incorporate these materials into a future biorefinery.
Keywords: Biomass; Biorefinery; Emissions factor; Energy; Thermochemical conversion